PENGARUH PENGGUNAAN MEDIA RODA BACA TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS I DI SD NO. 2 DALUNG TAHUN PELAJARAN 2025/2026 - Listia Manik, Ni Luh Putri; I Gusti Ngurah Triyana; I Made Sukariawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The focus of this research is motivated by the low reading literacy skills of first-grade students at SD No. 2 Dalung. Based on field observations, a phenomenon was discovered where most students still face obstacles in distinguishing similar letter shapes, experience difficulty pronouncing consonantvowel combinations, and show low enthusiasm toward conventional learning media. The objective of this quantitative research, which employs a Quasi-Experimental design, is to determine the effectiveness of